MACROPHAGE AND CYTOKINE PROFILES OF BRONCHOALVEOLAR LAVAGE IN NEW AND RELAPSING RESPIRATORY SARCOIDOSIS - N. G. Demyanenko; L. N. Lepekha; E. I. Shmelev; M. M. Averbakh; T. A. Statsuk; I. V. Sivokozov (Туберкулез и болезни лёгких)
Goal of the study: to investigate structural and functional specific features of macrophages and cytokine profiles of bronchoalveolar lavage in new and relapsing respiratory sarcoidosis (RS).Materials and methods. The study included comparative light optical and electronic microscopic examinations of macrophages, macrophage formula and cytokine profile of bronchoalveolar lavage in 120 patients suffering from different forms of RS. It was found that in case of new RS mostly macrophages of M1 phenotype were detected in the lavage. They had high level of IL-8, IL-2, IL-1β production and ultrastructural signs of hypersecretion which was especially typical of platycytes. High level of IL-4, IL-5 content is typical of relapsing sarcoidosis: additionally to macrophages of M1 phenotype, there are macrophages of M2 phenotype with ultrastructural signs of phagocytic function which can be used for diagnostics of this form of RS.